2007
DOI: 10.1111/j.1467-8624.2007.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Language and Theory of Mind: Meta‐Analysis of the Relation Between Language Ability and False‐belief Understanding

Abstract: Numerous studies show that children's language ability is related to false-belief understanding. However, there is considerable variation in the size of the correlation reported. Using data from 104 studies (N=8,891), this meta-analysis determines the strength of the relation in children under age 7 and examines moderators that may account for the variability across studies--including aspect of language ability assessed, type of false-belief task used, and direction of effect. The results indicate a moderate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

62
717
10
51

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 928 publications
(840 citation statements)
references
References 117 publications
62
717
10
51
Order By: Relevance
“…Therefore, emotion language is not just a component of emotional competence; it is also a manifestation of 'theory of mind ' (ToM), the child's growing awareness of the existence of internal states in itself and in others (Harris, 1989 ;. Both cross-sectional (Dunn, Brown & Beardsale, 1991 ;Astington & Jenkins, 1999 ;de Villiers & de Villiers, 2000 ;Adriàn, Clemente, Villanueva & Rieffe, 2005;Astington & Baird, 2005) and training (Lohmann & Tomasello, 2003 ;Hale & Tager-Flusberg, 2003 ;Grazzani Gavazzi & Ornaghi, 2008) studies have shown that language plays a crucial role in fostering children's understanding of the mind (Milligan, Astington & Dack, 2007). Recent findings support the hypothesis of a bi-directional relationship between theory of mind and language (Slade & Ruffman, 2005) although the effect of language on theory of mind seems to be stronger than the other way round.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, emotion language is not just a component of emotional competence; it is also a manifestation of 'theory of mind ' (ToM), the child's growing awareness of the existence of internal states in itself and in others (Harris, 1989 ;. Both cross-sectional (Dunn, Brown & Beardsale, 1991 ;Astington & Jenkins, 1999 ;de Villiers & de Villiers, 2000 ;Adriàn, Clemente, Villanueva & Rieffe, 2005;Astington & Baird, 2005) and training (Lohmann & Tomasello, 2003 ;Hale & Tager-Flusberg, 2003 ;Grazzani Gavazzi & Ornaghi, 2008) studies have shown that language plays a crucial role in fostering children's understanding of the mind (Milligan, Astington & Dack, 2007). Recent findings support the hypothesis of a bi-directional relationship between theory of mind and language (Slade & Ruffman, 2005) although the effect of language on theory of mind seems to be stronger than the other way round.…”
Section: Introductionmentioning
confidence: 88%
“…This task is representative of the major change in theory of mind capacities that start emerging in children at around 4 years of age (Wellman et al 2001). Similar tasks have been used in other studies and are part of commonly used theory of mind test batteries (Cassidy et al 2005;Milligan et al 2007). The stimulus was a sponge covered with granite gray paint to make it look like a rock.…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…These hypotheses were examined while including a measure of language skills as a control variable in all analyses. The positive relation between language development and theory of mind is firmly established (Astington 2001;Milligan et al 2007). It is thus essential to control for language to eliminate the possibility that the contribution of theory of mind to reactive or proactive aggression could be better explained by a child's language skills -or lack thereof.…”
mentioning
confidence: 99%
“…Language and theory of mind in autism spectrum disorder 8 unexpected contents (Perner et al, 1987) Although all participants in the current study completed both false belief tasks, given that each task entails different cognitive demands, the results from each were considered separately, rather than as a composite. For example, whereas the SallyAnne task involves a narrative and a relatively simple test question, the Smarties task does not involve a narrative but involves a more complex test question (Milligan, Astington, & Dack, 2007). In typical development, it is generally assumed that a shift to a representational ToM underlies successful false belief task performance, regardless of task-specific factors (Wellman et al, 2001).…”
mentioning
confidence: 99%